The Impact of Technological Advancement in the Use of the SIREKAP Program in the 2024 Elections is studied according to the Principles of Public Accountability for Democratic Election Calculations - Masripa Siti Zahra; Dedi Mulyadi; Alya Khansa Syahla (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
The application of technology in the general election (Pemilu) process has great potential to increase efficiency and transparency, but also raises a number of challenges related to data security and integrity. This article examines the impact of using the Election Recapitulation Information System Program (SIREKAP) in the 2024 Election in Indonesia, with a focus on aspects of public accountability and democratic election calculations. This research uses a normative juridical approach by analyzing related laws and regulations, such as the Election Law and General Election Commission Regulations (PKPU), as well as secondary sources such as books and scientific journals. The research results show that SIREKAP is a solution to the challenges in the manual vote recapitulation process, with the aim of speeding up the process, increasing accuracy and increasing transparency. However, this program is also faced with a number of problems, including data errors, access and connection problems, and cyber security issues. To overcome this problem, concrete steps are needed, such as intensive training for voting organizers, expanding internet network infrastructure, and strengthening system security. In conclusion, the use of SIREKAP in the 2024 Election has the potential to increase the efficiency and transparency of the election process, but also presents a number of challenges. Close collaboration between governments, legal entities and civil society is necessary to ensure successful implementation and maintain security. By implementing the right solution, it is hoped that SIREKAP can become an effective tool in maintaining the integrity and transparency of the election process in the future.